Elastolytic activity of sputum and its relation to purulence and to lung function in patients with bronchiectasis. - R A Stockley; Susan L. Hill; H M Morrison; C. M. Starkie (1984)
Sputum samples from 34 patients with bronchiectasis were assessed subjectively and the results related to objective measurements of elastase activity and albumin content. The results suggest that the macroscopic appearance of the sample is related to the elastase content. 88.7% of the purulent samples but none of the mucoid samples showing elastase activity. The macroscopic appearance was also associated with changes in protein transudation into the secretions. The median sputum: serum albumin concentration ratio was 0.71 X 10(-2) (range 0.22-4.7) in the mucoid samples but was greater in purulent samples (p less than 0.005), with a median value of 1.52 X 10(-2) (range 0.55-12.72), suggesting that purulence in the stable state was associated with low grade pulmonary inflammation or epithelial damage or both. Abnormalities of air flow were found in 24 of the patients (70.6%) but there was a significantly higher ratio of residual volume to total lung capacity (p less than 0.025) in patients who regularly produced purulent sputum (mean (SD) RV/TLC 44.4% (9.0%] than in those with mucoid or mucopurulent secretions (38.0% (9.9%]. A similar difference was found between those who produced elastase positive secretions and those who produced elastase negative ones.